PENAMBAHAN OCTANE BOOSTER PADA PERTALITE TERHADAP KINERJA MESIN DAN KONSUMSI BAHAN BAKAR MESIN HONDA BEAT 2014 - Yudan Kurniawan, Mohammad; Margianto; Nur Robbi (RING ME, 2023)
The purpose of this study was to evaluate the effect of adding Pertalite to fuel on engine performance and fuel consumption of Honda Beat 2014 motorcycle engines. This study used three octane booster mixtures to examine the effect of mixtures added to Pertalite fuel on engine performance of the Honda Beat 2014 In addition, the addition of an octane booster also increases fuel consumption efficiency which significantly reduces the amount of fuel consumed by the engine and produces environmentally friendly emissions when the number of octane boosters increases. Based on these findings, it was concluded that the use of Pertalite octane accelerator fuel could improve the engine performance of the Honda Beat 2014 motorcycle and reduce fuel consumption. Therefore, using an octane booster can be an attractive option for Honda Beat 2014 motorcycle owners who want to improve engine performance, optimize fuel economy, but produce emissions that are not environmentally friendly.